(untitled) (Research, Society and Development, 2022)
The quality of Nile Tilapia fillets (Oreochromis niloticus) stored under refrigeration temperatures of -1 °C and 4 °C was evaluated through physical and chemical analyzes (pH, water activity and instrumental color) and microbiological (Staphylococcus positive coagulase, detection of Salmonella spp. and E. coli count), with the objective of determining the time for its commercialization. The fillets were donated by a slaughterhouse in the greater Dourados region - MS. The analyzes followed were conducted according to official methods. In the 12th day an unpleasant odor and mucus appeared in the surface of the fillets that were stored in temperatures between 0 to 4.5ºC. The water activity was higher than 0.95 and pH values got higher than 5.2, because of these factors the products should be stored at the temperature of ≤ 5ºC. By the end of the analysis time there was an increased red intensity in the white part (PB) in both temperatures (-1ºC and 4ºC), and the same effect happened in the line of blood (LS) at -1ºC, but it was not evidenced at 4ºC. The intensity of yellow was also increased in the analyzed regions (PB and LS). The samples met the Brazilian legislation in terms of microbiological standards. It is concluded that the shelf life of fillets stored at 4°C is up to a maximum of 11 days and the products stored below -1°C is up to 20 days.